Pleural effusion presenting as mediastinal widening - Mohapatra, Prasanta R. (Medknow Publications & Media Pvt Ltd, 2013)
We report a case of middle-aged female presenting with mediastinal widening on chest radiograph owing to pleural effusion. The pleural effusion presenting as mediastinal widening on chest radiograph is rarely reported.